Molecular Biology of Bamboo mosaic Virus - A Type Member of the Potexvirus Genus - Na-Sheng Lin (Frontiers Research Topics, 2018)
The flexible filamentous plant viruses are responsible for more than half of all agricultural loss worldwide. Potexvirus is one of the two most important flexible filamentous plant viruses. Bamboo mosaic virus (BaMV), a single-stranded positive-sense RNA virus, is a member of the Potexvirus genus of Alphaflexiviridae. It can infect at least 12 species of bamboo, causing a huge economic impact on the bamboo industry in Taiwan. The study of BaMV did not start extensively until the completion of the full-length sequencing of genomic RNA of BaMV and generation of the BaMV infectious cDNA clone in the early 1990s. Since then, BaMV has been extensively studied at the molecular, cellular and ecological level, covering both basic and applied researches, by a group of researchers in Taiwan. In this eBook, the content comprises 6 reviews and 4 articles. Seven of them are involved in the infection of BaMV covering viral RNA replication, viral RNA trafficking, and the host factors. Two of them are related to the vector transmission and the ecology of BaMV. The last one is the application of using BaMV as a viral vector to produce vaccines in plants.